Efficiency of IPNS-based chemical fertilizer application in wet land rice (Bangladesh Journal of Agricultural Research, 2010)
A field trial was conducted to validate some fertilizer application approaches for Boro-Green manure (GM) -T. Aman cropping system at the Bangladesh Rice Research Institute (BRRI) Farm, Gazipur (AEZ-28: high land) during the period from Boro 1999-2000 to T. Arnan 2000. Five different application approaches of inorganic and organic fertilizers along with their residual values were evaluated. A positive effect of GM on the yield of T. Aman rice was observed. Application of cowdung (CD) @ 6 t/ha (at 15 % moisture) along with integrated plant nutrient system (IPNS) based chemical fertilizer in Boro season followed by green manuring with dhaincha (in Kharif-l season) and then growing T. Aman rice (in Kharif-ll season) with reduced doses of chemical fertilizer (60% N, 50% P, 50% K, and 50% S) substantially increased grain yield and narrowed down the N, P, and K balance in soil. This fertilizer application approach may be practiced for sustainable crop production. No appreciable yield loss in T. Arnan rice (2nd crop) occurred due to the application of reduced doses of P, K, S, and Zn indicating the beneficial residual effect of fertilizer applied to the first crop (Boro rice) of the cropping pattern. The N uptake was in excess of the N added as fertilizer. An improved balance of P, S, and Zn was observed. But the K balance was negative. However, application of cowdung and incorporation of dhaincha slightly improved the K balance of the soil. The highest gross return of Tk. 86,270 was obtained with the above practice (treatment T4)Key Words: Chemical fertilizer; application; wet land rice.DOI: 10.3329/bjar.v34i1.5747Bangladesh J. Agril. Res. 34(1) : 5-13, March 2009